MATH SOLVE

2 months ago

Q:
# Samuel is solving the equation 3(x-1)+4=2-(x+3) Which equivalent equations might Samuel use? Check all that apply.A. 3x-3+4=2-x-3B. 3x-1+4=2-x+3C. 3x-3+4=2-x+3D. 3x+1=-x-1E. 3x+3=-x+5F. 3x+1=-x+5

Accepted Solution

A:

Answer:Option A and D are correct.[tex]3x -3 +4 =2-x-3[/tex] and [tex]3x +1 = -x -1[/tex] are the equivalent equations might Samuel useStep-by-step explanation:Given the equation: [tex]3(x-1)+4 = 2-(x+3)[/tex]using distributive property; [tex]a\cdot (b+c) = a\cdot b+ a\cdot c[/tex]3x - 3 + 4 = 2- x -3Like terms are those terms that have same variables or powerCombine like terms on each side;3x + 1 = -x -1Subtract 1 from both sides we get;3x = -x -2or4x = -2Divide both sides by 4 we get;[tex]x = -\frac{2}{4} = -\frac{1}{2}[/tex]Therefore, the equivalent equations might Samuel use are; [tex]3x -3 +4 =2-x-3[/tex] and [tex]3x +1 = -x -1[/tex]